The Impact of the Implementation of Corporate Zakat on Corporate Financial and Social Performance - Hasanudin; Hermansyah, Yus; Hariadi, Fadli; Ardiansyah, Dian (DPPM Universitas Pelita Bangsa, 2023)
The impact of the company's zakat application on performance can be seen from several aspects, both directly and indirectly. The company's zakat issued can reduce the tax burden that must be paid, because zakat can be deducted from taxable income in several countries, including Indonesia. This study tries to outline the impact of the implementation of corporate zakat on the company's financial and social performance. The research method used is library research with a qualitative approach. The results of the study show that companies can effectively integrate these practices into their financial and CSR strategies, as well as harness the potential to increase their positive impact on society and the economy more broadly. The integration of corporate financial and social performance is an integral part of a comprehensive and sustainable business strategy. Companies that can strike a balance between the two tend to be more successful in creating long-term value, both for their internal and external stakeholders. Therefore, the integration of corporate zakat in business and CSR strategies needs to be managed properly to maximize its positive benefits while maintaining a healthy financial balance.